Cinema, aspirins and vultures [videorecording (DVD)] - Gomes, Marcelo, 1963-; Gomes, Marcelo, 1963-; Miguel, João, 1970-; Ketnath, Peter (Global Film Initiative ; First Run Features [distributor, 2007)
During World War II, Ranulpho hitches a ride with Johan, an aspirin salesman running from the German draft. But as Brazil is about to enter the war against Germany, Johan must quickly run or his days of freedom may be numbered.